2022
DOI: 10.1371/journal.pgph.0001028
|View full text |Cite
|
Sign up to set email alerts
|

Geographic barriers to care persist at the community healthcare level: Evidence from rural Madagascar

Abstract: Geographic distance is a critical barrier to healthcare access, particularly for rural communities with poor transportation infrastructure who rely on non-motorized transportation. There is broad consensus on the importance of community health workers (CHWs) to reduce the effects of geographic isolation on healthcare access. Due to a lack of fine-scale spatial data and individual patient records, little is known about the precise effects of CHWs on removing geographic barriers at this level of the healthcare s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…This spatial distribution results in greater availability of medical services within close proximity in urban areas, facilitating prompt access. This may suggest that rural areas have fewer healthcare facilities, and individuals might need to travel more distances to reach the nearest center [34].…”
Section: Discussionmentioning
confidence: 99%
“…This spatial distribution results in greater availability of medical services within close proximity in urban areas, facilitating prompt access. This may suggest that rural areas have fewer healthcare facilities, and individuals might need to travel more distances to reach the nearest center [34].…”
Section: Discussionmentioning
confidence: 99%
“…paid by households). 7 The third problem relates to the travel and waiting times required to access public services; these represent significant 'opportunity costs', which may change over time depending on the State of public administrations, roads, or climatic variations (Evans et al, 2022).…”
Section: Household Surveys Microeconomic Analyses and The Mirage Of A...mentioning
confidence: 99%
“…By way of example, health represents 1 % of expenditure in the Malagasy CPI basket, whereas according to the World Health Organization (WHO)'s sector accounts, in 2020, 34% of the country's health expenditures were "out-of-pocket expenditure" (i.e., paid by households) 7 . The third problem relates to the travel and waiting times required to access public services; these represent significant "opportunity costs", which may change over time depending on the State of public administrations, roads or climatic variations (Evans et al, 2022).…”
Section: Household Surveys Microeconomic Analyses and The Mirage Of A...mentioning
confidence: 99%
“…Access to health care is a major problem, including at very local scales such as the access to community health workers. Indeed, a recent study showed that the consultation rate of community health workers was reduced by 28.1% for each increase of 1 km in the distance with the patient’s house [ 19 ]. Similarly, access to PEP remains a major issue in Madagascar [ 12 ].…”
Section: Introductionmentioning
confidence: 99%